Total least squares problems on infinite dimensional spaces. (15th March 2021) - Contino, Maximiliano; Fongi, Guillermina; Maestripieri, Alejandra; Muro, Santiago
Abstract: We study weighted total least squares problems on infinite dimensional spaces. We present some necessary and sufficient conditions for the regularized problem to have a solution. The existence of solution can also be assured for the regularized minimization problem with a constraint to special subsets. Furthermore, we show that a regularization in infinite dimensional total least squares problems is necessary, since in most cases the problem without regularization does not admit a solution.